Analisis Fisika Inti Pada Teknik Radioterapi untuk Pengobatan Tumor - Rahmatiah; Dzahratis Syita; Selvi (Physics Department, Faculty of Mathematics and Natural Sciences, Universitas Negeri Makassar, 2026)
Radiotherapy is one of the main modalities in tumor treatment that utilizes the principles of nuclear physics. This article aims to review and analyze the application of nuclear physics in radiotherapy techniques for tumor treatment, focusing on the identification of radioactive isotopes used, the type of radiation emitted, and the mechanism of radiation interaction with tumor tissue. The method used is a literature review of various relevant scientific articles. The results show that external beam radiotherapy (EBRT) uses a Cobalt-60 (Co-60) source that emits gamma rays with energies of 1.17 MeV and 1.33 MeV, while brachytherapy uses isotopes such as Iridium-192 (Ir-192) with an average gamma emission of 380 keV and Iodine-125 (I-125) with gamma emissions of 27–35 keV. All three isotopes are produced through neutron activation in nuclear reactors. The generated radiation works by breaking the DNA chains of tumor cells, preventing their replication. Modern techniques such as IMRT, 3DCRT, and IGRT allow high precision in dose delivery, minimizing damage to healthy tissue surrounding the tumor. It is concluded that a deep understanding of nuclear physics is crucial in the effective and safe application of radiotherapy.